Hybrid Intrusion Detection System Using Machine Learning Techniques in Cloud Computing Environments - Aljamal, Ibraheem; Tekeoglu, Ali; Bekiroglu, Korkut; Sengupta, Saumendra (2019 IEEE 17th International Conference on Software Engineering Research, Management and Applications (SERA), 2019)
Intrusion detection is one essential tool towards building secure and trustworthy Cloud computing environment, given the ubiquitous presence of cyber attacks that proliferate rapidly and morph dynamically. In our current working paradigm of resource, platform and service consolidations, Cloud Computing provides a significant improvement in the cost metrics via dynamic provisioning of IT services. Since almost all cloud computing networks lean on providing their services through Internet, they are prone to experience variety of security issues. Therefore, in cloud environments, it is necessary to deploy an Intrusion Detection System (IDS) to detect new and unknown attacks in addition to signature based known attacks, with high accuracy. In our deliberation we assume that a system or a network "anomalous" event is synonymous to an "intrusion" event when there is a significant departure in one or more underlying system or network activities. There are couple of recently proposed ideas that aim to develop a hybrid detection mechanism, combining advantages of signature-based detection schemes with the ability to detect unknown attacks based on anomalies. In this work, we propose a network based anomaly detection system at the Cloud Hypervisor level that utilizes a hybrid algorithm: a combination of K-means clustering algorithm and SVM classification algorithm, to improve the accuracy of the anomaly detection system. Dataset from UNSW-NB15 study is used to evaluate the proposed approach and results are compared with previous studies. The accuracy for our proposed K-means clustering model is slightly higher than others. However, the accuracy we obtained from the SVM model is still low for supervised techniques.